Pathology and mechanisms of cochlear aging. Issue 9 (7th May 2019) - Keithley, Elizabeth M.
Abstract: Presbycusis, or age‐related hearing loss (ARHL), occurs in most mammals with variations in the age of onset, rate of decline, and magnitude of degeneration in the central nervous system and inner ear. The affected cochlear structures include the stria vascularis and its vasculature, spiral ligament, sensory hair cells and auditory neurons. Dysfunction of the stria vascularis results in a reduced endocochlear potential. Without this potential, the cochlear amplification provided by the electro‐motility of the outer hair cells is insufficient, and a high‐frequency hearing‐loss results. Degeneration of the sensory cells, especially the outer hair cells also leads to hearing loss due to lack of amplification. Neuronal degeneration, another hallmark of ARHL, most likely underlies difficulties with speech discrimination, especially in noisy environments. Noise exposure is a major cause of ARHL. It is well‐known to cause sensory cell degeneration, especially the outer hair cells at the high frequency end of the cochlea. Even loud, but not uncomfortable, sound levels can lead to synaptopathy and ultimately neuronal degeneration. Even in the absence of a noisy environment, aged cells degenerate. This pathology most likely results from damage to mitochondria and contributes to degenerative changes in the stria vascularis, hair cells, and neurons. The genetic underpinnings of ARHL are still unknown and most likely involve various combinations of genes. At present, the only effective strategy for reducing ARHL is prevention of noise exposure. If future strategies can improve mitochondrial activity and reduce oxidative damage in old age, these should also bring relief.